Application of Information System in the Field of Graphic Design - T Rohmawati; M Fitroh; A Faadhilah; N Nuha; N P Dewi (International Journal of Education, Information Technology, and Others, 2021)
In this digital era, visual communication businesses such as graphic design are among the areas of business that are in great demand. However, the ordering is limited to via telephone or coming directly to the place of business. The purpose of this research is to facilitate business in graphic design by including an information system to facilitate and increase the business's performance. This research used qualitative methods and was supported by the waterfall system as the development method. The use of management resources and information technology services is to support business processes in the organization. The results show that this application makes it producers easier to find consumers, makes business management better, as well as facilitates consumer orders. The conclusion from the installation of information systems for graphic design businesses has a positive impact in terms of bookkeeping, warehouse expenses, the relationship between customers and producers, as well as to see the development of the businesses easily and clearly